2014
DOI: 10.1080/23279095.2014.881367
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Inferential Abilities Based on Pictorial Stimuli in Patients With Right-Hemisphere Damage

Abstract: Inferences are mental representations derived from the interaction between explicit linguistic information and an individual's world knowledge. The right hemisphere (RH) is the main region responsible for this ability, particularly with regard to pictorial stimuli. The aims of this study were to evaluate the performance of RH-damaged patients on an inference comprehension task based on pictorial stimuli and to compare the effect of different lesion sites on this performance. We compared the inferential abiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
5
0
2
Order By: Relevance
“…The types of signs featured in the image are first identified: icon signs (drawing), plastic signs (characteristics such as color, shape and texture) and language sign (related to verbal language) (16) . The image is then processed using inferences, which are mental representations the individual has based on their world knowledge (17) . We believe that the group data collection process with the volunteers elicited this processing: the image was presented to the individuals who then had to interpret it.…”
Section: Discussionmentioning
confidence: 99%
“…The types of signs featured in the image are first identified: icon signs (drawing), plastic signs (characteristics such as color, shape and texture) and language sign (related to verbal language) (16) . The image is then processed using inferences, which are mental representations the individual has based on their world knowledge (17) . We believe that the group data collection process with the volunteers elicited this processing: the image was presented to the individuals who then had to interpret it.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, two studies have reported the ability of RH-damaged patients to generate inferences from visual stimuli. 11 , 12 In the first study, 11 the authors evaluated the ability of RH-damaged subjects to generate inferences from visual stimuli, controlling for the complexity of the stimuli and educational level. They found that patients with higher educational level performed better than those with lower schooling; also, those pictures with greater visual complexity (i.e., more visual elements in the scene) and that were more complex (i.e., with a higher number of associations) presented more difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, inferential complexity had a greater impact on the performance of most participants than visual complexity, both for controls and RH-damaged patients. The second study 12 compared the inferential abilities of healthy and RH-damaged individuals using pictorial stimuli. The authors found that RH-damaged patients performed poorer than controls on comprehending logical and pragmatic visual inferences, independently of lesion site.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto aos aspectos pragmático-inferenciais, são observadas dificuldades na compreensão de sentidos não-literais, intenções comunicativas, humor e moral em fábulas, sarcasmos e ironia, metáforas, atos de fala indiretos e inferências (Winner, Gardner, 1977;Hisrt et al, 1984;Brookshire, Nicholas, 1984;Brownell et al, 1986;Weylman, 1989;Beeman, 1993;Bottini et al, 1994;Chantraine et al, 1998;Tompkins et al, 2001;Champagne et al, 2003a ;Gagnon et al, 2003;Keil et al, 2005;Cheang, Pell, 2006;Blake, 2009;Ribeiro et al, 2015).…”
Section: Alterações Da Comunicação Decorrentes De Lesão Em Hemisfériounclassified
“…A literatura mostra de forma consistente que indivíduos com lesão de HD (LHD) apresentam dificuldades na realização de inferências quando comparados aos indivíduos normais (Brownell et al, 1986;Beeman, 1993;; Tompkins et al, 2001;Keil et al, 2005;Blake, 2009;Ribeiro et al, 2015). No entanto, alguns estudos comparativos mostram que pacientes com lesão em HE (LHE) também apresentam dificuldades no processamento inferencial (Saldert, Ahle´n, 2007;Goel et al, 2007;Hamel, Joanette, 2007).…”
Section: Introductionunclassified